What Is Wrong With Grade Inflation (if Anything)? - Finefter-Rosenbluh, Ilana; Levinson, Meira (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2015)
Grade inflation is a global phenomenon that has garnered widespread condemnation among educators, researchers, and the public. Yet, few have deliberated over the ethics of grading, let alone the ethics of grade inflation.  The purpose of this paper is to map out and examine the ethics of grade inflation. By way of beginning, we clarify why grade inflation is a problem of practical ethics embedded in contemporary social practice. Then, we illuminate three different aspects of grade inflation—longitudinal, compressed, and comparative—and explore the ethical dilemmas that each one raises.  We demonstrate how these three aspects may be seen as corresponding to three different victims of grade inflation—individuals, institutions, and society—and hence also to three potential agents of harm—teachers, schools, and educational systems. Next, we reflect upon various compelling reasons that these agents inflate grades, whether from an ethic of care, fiduciary responsibility, or simple self-preservation. Subsequently, we consider a variety of means of combatting grade inflation, and invite more educators and philosophers to delve into the complex practical ethics of grade inflation.